The Robbery of the Hoja Ahmad Yassavi Complex by the Russian Colonials - Sadullayev Sanjar (Genius Publishing Group, 2022)
Since the second half of the XIX century, not only the material but also the spiritual and cultural wealth of the Central Asian region, which was invaded by the Russian Empire, has been plundered by the colonialists. One of them is the famous Ahmad Yassavi complex (mausoleum-mosque) and its unique historical and cultural artifacts
Keywords: Empire; Mausoleum; Mosque; Candlestick